Planar Large Core Polymer Optical 1x2 and 1x4 Splitters Connectable to Plastic Optical Fiber - Prajzler, Vaclav; Neruda, Milos; Spirkova, Jarmila (Společnost pro radioelektronické inženýrství, 2013)
We report about new approach to design and fabricate multimode 1 x 2 and 1 x 4 Y optical planar power splitter suitable for low-cost short distance optical network. The splitters were designed by beam propagation method using BeamPROP™ software. The dimensions of the splitters were optimized for connecting standard plastic optical fibre with 1 mm diameter. New Norland Optical Adhesives 1625 glues were used as optical waveguide layers and the design structures were completed by CNC engraving on poly(methyl methacrylate) substrate. The best parameters that were achieved with 1x2 splitter were insertion loss around 4.1dB at 650 nm and the coupling ratio 52:48; the best one of the 1x4 splitters had at 650 nm insertion loss around 17.6 dB.
Keywords: Multimode 1x4 coupler; optical planar waveguide; polymer; beam propagation method